The inductive role of Wnt-β-Catenin signaling in the formation of oral apparatus - Lin, Congxing (2011)
Proper patterning and growth of oral structures including teeth, tongue, and palate rely on epithelial-mesenchymal interactions involving coordinated regulation of signal transduction. Understanding molecular mechanisms underpinning oral-facial development will provide novel insights into the etiology of common congenital defects such as cleft palate. In this study, we report that ablating Wnt signaling in the oral epithelium blocks the formation of palatal rugae, which are a set of specialized ectodermal appendages serving as Shh signaling centers during development and niches for sensory cells and possibly neural crest related stem cells in adults. Lack of rugae is also associated with retarded anteroposterior extension of the hard palate and precocious mid-line fusion. These data implicate an obligatory role for canonical Wnt signaling in rugae development. Based on this complex phenotype, we propose that the sequential addition of rugae and its morphogen Shh, is intrinsically coupled to the elongation of the hard palate, and is critical for modulating the growth orientation of palatal shelves. In addition, we observe a unique cleft palate phenotype at the anterior end of the secondary palate, which is likely caused by the severely underdeveloped primary palate in these mutants. Last but not least, we also discover that both Wnt and Shh signalings are essential for tongue development. We provide genetic evidence that disruption of either signaling pathway results in severe microglossia. Altogether, we demonstrate a dynamic role for Wnt-β-Catenin signaling in the development of the oral apparatus.